Marrow Adipose Tissue Expansion Coincides with Insulin Resistance in MAGP1-Deficient Mice - Walji, Tezin A.; Turecamo, Sarah E.; Sanchez, Alejandro Coca; Anthony, Bryan A.; Abou-Ezzi, Grazia; Scheller, Erica L.; Link, Daniel C.; Mecham, Robert P.; Craft, Clarissa S. (Frontiers in Endocrinology, 2016)
Marrow adipose tissue (MAT) is an endocrine organ with the potential to influence skeletal remodeling and hematopoiesis. Pathologic MAT expansion has been studied in the context of severe metabolic challenge, including caloric restriction, high fat diet feeding, and leptin deficiency. However, the rapid change in peripheral fat and glucose metabolism associated with these models impedes our ability to examine which metabolic parameters precede or coincide with MAT expansion. Microfibril-associated glycoprotein-1 (MAGP1) is a matricellular protein that influences cellular processes by tethering signaling molecules to extracellular matrix structures. MAGP1-deficient (Mfap2−/−) mice display a progressive excess adiposity phenotype, which precedes insulin resistance and occurs without changes in caloric intake or ambulation. Mfap2−/− mice were, therefore, used as a model to associate parameters of metabolic disease, bone remodeling, and hematopoiesis with MAT expansion. Marrow adiposity was normal in Mfap2−/− mice until 6 months of age; however, by 10 months, marrow fat volume had increased fivefold relative to wild-type control at the same age. Increased gonadal fat pad mass and hyperglycemia were detectable in Mfap2−/− mice by 2 months, but peaked by 6 months. The development of insulin resistance coincided with MAT expansion. Longitudinal characterization of bone mass demonstrated a disconnection in MAT volume and bone volume. Specifically, Mfap2−/− mice had reduced trabecular bone volume by 2 months, but this phenotype did not progress with age or MAT expansion. Interestingly, MAT expansion in the 10-month-old Mfap2−/− mice was associated with modest alterations in basal hematopoiesis, including a shift from granulopoiesis to B lymphopoiesis. Together, these findings indicate MAT expansion is coincident with insulin resistance, but not excess peripheral adiposity or hyperglycemia in Mfap2−/− mice; and substantial MAT accumulation does not necessitate a proportional decrease in either bone mass or bone marrow cellularity.